Outcomes of vitreoretinal surgery for retinal detachment after LASIK for myopia (2006)
PURPOSE. To report and compare outcomes of vitreoretinal surgery for repair of retinal detachment in myopic patients with and without previous laser-assisted in situ keratomileusis (LASIK). METHODS. This is a descriptive retrospective observational study with a control group for comparison that consisted of the analysis of clinical and surgical charts of patients who underwent vitreoretinal procedures for retinal detachment at the Fundación Oftalmológica Nacional between January 1995 and December 2002. The authors identified those myopic patients who had previous history of LASIK and an age- and myopia-matched control group without refractive surgery. RESULTS. The sample contains 24 myopic eyes of 22 patients with previous LASIK and 23 myopic eyes without previous LASIK in the control group, matched by age and myopia. Mean refractive error was -9.4 D before LASIK for the cases group and -11.2 for the control group. Poor preoperative best-corrected visual acuity was present in 71% of cases and 61% of controls (p=0.489). Macula off retinal detachment was found in 17 eyes in both groups. Five eyes required at least two procedures, achieving 91% (20 eyes) reattachments at the end of follow-up in each group. Final best-corrected visual acuity was better than 20/100 in 15 eyes (62.5%) in the LASIK group and 17 eyes (74%) in the control group (p=0.659). CONCLUSIONS. Retinal detachment in patients with previous myopic LASIK has similar characteristics as in myopic patients without refractive surgery. Current vitreoretinal surgery is of good prognosis as the retina was successfully reattached in most cases in both groups. © Wichtig Editore, 2006.